2020
DOI: 10.1007/s10266-020-00517-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of cytokine patterns and clinical/laboratory parameters, medication and periodontal burden in patients with rheumatoid arthritis (RA)

Abstract: To evaluate serum levels of the following cytokines in rheumatoid arthritis subjects with periodontal disease: Interleukin-6,-10,-17, and-23. Patients with rheumatoid arthritis frequently suffer from periodontal disease. Both diseases partly result from a dysregulated immune response. The current study aimed to quantify Interleukin-6,-10,-17, and-23 levels in rheumatoid arthritis. It should be investigated if the periodontal disease would have additional modifying effects. A total of 157 patients were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Regarding these findings, Ridgley LA et al 39 proposes that the expression of some cytokines, such as IL‐17A, is inversely proportional to the course and chronicity of arthritis rheumatoid and IL‐17 is expressed mainly in the preclinical phase and decreases according to the chronicity of RA. Moreover, the IL‐17A levels in RAP patients are diminished when they have high disease activity (DAS28‐ESR), according to Patschan S et al 29 Interestingly, the P and RAP group showed similar behavior since IL‐17A decreases when an advanced periodontitis stage is found (Stage III). This suggests that IL‐17 tends to modulate its expression downward as disease activity progresses in RAP.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Regarding these findings, Ridgley LA et al 39 proposes that the expression of some cytokines, such as IL‐17A, is inversely proportional to the course and chronicity of arthritis rheumatoid and IL‐17 is expressed mainly in the preclinical phase and decreases according to the chronicity of RA. Moreover, the IL‐17A levels in RAP patients are diminished when they have high disease activity (DAS28‐ESR), according to Patschan S et al 29 Interestingly, the P and RAP group showed similar behavior since IL‐17A decreases when an advanced periodontitis stage is found (Stage III). This suggests that IL‐17 tends to modulate its expression downward as disease activity progresses in RAP.…”
Section: Discussionmentioning
confidence: 90%
“…In this context, IL‐23/IL‐17 axis in RA and P has also been studied in different samples, 13–22 as well as its receptors, IL‐23R, and IL‐17RA 23–26 . In patients with rheumatoid arthritis who present periodontitis, IL‐17 has been reported in the gingival crevicular fluid (GCF) and serum, 27 while IL‐23 has been reported in saliva, 28 likewise IL‐23 and IL‐17 in serum 29 . It has also been described that IL‐23 and IL‐17 levels in GCF, saliva, serum, and plasma are elevated in both periodontitis patients and 17,18,20–22,24 patients with rheumatoid arthritis 13,15,16,25,27,30,31 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, while csDMARDS and biological DMARDS have shown their efficacy in the treatment of RA, insufficient evidence is available to estimate the effect of such anti-rheumatic treatment on the periodontal condition of RA patients [ 11 , 12 ]. There is some evidence that treatment with anti-TNF might initially improve bleeding on probing and the gingival index, and later on it might improve bleeding on probing pocket depth and clinical attachment level [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A higher prevalence of tooth loss in individuals suffering from RA has already been presumed in previous studies [ 8 , 21 , 22 , 23 ]. Furthermore, missing teeth were found to be a potential influential factor on proinflammatory cytokines in RA patients [ 24 ]. Additionally, a Japanese study reported tooth loss to be related to stronger RA therapies (medication), independent of the disease activity of RA [ 6 ].…”
Section: Discussionmentioning
confidence: 99%